2018
DOI: 10.1177/1687814018785092
|View full text |Cite
|
Sign up to set email alerts
|

Study on evacuation simulation under crowd-diversion condition

Abstract: With the increasing number of domestic buildings, the importance of safety evacuation in case of fire in the buildings has been aware. Occupants in a building will crowd at exit(s) when they evacuate in disasters. The content of this study includes the following: (1) to conduct a literature review on severe stampedes in history, identifying the number of casualties, and to explore existing research on crowd evacuation; (2) to examine the applicability of software packages EXODUS and Unity for simulating occupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…The study proposed suggesting found paths over mobile messaging or broadcasting the paths to the people under evacuation. Another study [4] focused on evacuation in a simplified scenario covering a single indoor room with one exit. In such studies, simulation tools such as Unity [5] and EXODUS [6] are generally used.…”
Section: Unguided Crowd Evacuationmentioning
confidence: 99%
See 2 more Smart Citations
“…The study proposed suggesting found paths over mobile messaging or broadcasting the paths to the people under evacuation. Another study [4] focused on evacuation in a simplified scenario covering a single indoor room with one exit. In such studies, simulation tools such as Unity [5] and EXODUS [6] are generally used.…”
Section: Unguided Crowd Evacuationmentioning
confidence: 99%
“…As the rate of both natural and manmade disasters-fires, explosions, earthquakes, etc.-in populated areas is increasing, people are becoming more concerned about emergencies in which areas need to be evacuated promptly [1][2][3][4]. In such situations, people often panic, fearing losing their lives, and look for a quick exit to escape.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No entanto, esses treinamentos dificilmente são capazes de recriar as verdadeiras condições de pânico e as pessoas tendem a não considerar esse tipo de situação. Além disso, para essa ação é necessário envolver boa parte dos funcionários ou usuários do local (o que nem sempre é possível), bem como causar a Além disso, foram verificados em estudos que é possível, através do motor de jogo, fazer a simulação de evacuação de edifícios (CHIU et al, 2018;MÓL et al, 2011;XI e SMIDTH, 2015) e até mesmo juntar elementos de simulação de evacuação com o conceito de jogos sérios (ASANO et al, 2014).…”
unclassified
“…relação ao software de simulação, conforme exposto em um estudo feito porChiu et al (2018).Alguns pesquisadores propuseram a utilização de jogos de computador para treinar e também verificar o comportamento humano (CHITTARO eRANON, 2009; SMITH e TRENHOLME, 2009;KOBES et al, 2009;CORDEIRO et al, 2011b). Esse tipo de jogo, no qual o objetivo principal é a conscientização sobre certos problemas, ensino, educação, entre outras aplicações possíveis, e não o entretenimento, são conhecidos como jogos sérios(SUSI et al, 2007).…”
unclassified